Preferential deposition of visceral adipose tissue occurs due to physical inactivity - Belavý, D L; Möhlig, M; Pfeiffer, A F H; Felsenberg, D; Armbrecht, G (International Journal of Obesity, 2014)
We hypothesised that strict inactivity (bed rest) would lead to regional differences in fat deposition. Twenty-four male subjects underwent 60d bed rest and remained inactive ( n =9), performed resistance exercise plus whole-body vibration (RVE; n =7) or resistance exercise only (RE; n =8). Fat mass was assessed via dual X-ray absorptiometry. In the inactive subjects, fat deposition differed between body regions ( P =0.0005) with android region visceral adipose tissue increasing the most (+29% at the end of bed rest), followed by remainder of the trunk (from chin to the iliac crest; +10%) and the arms and legs (both +7%). Insulin sensitivity reduced in the inactive subjects at the end of bed rest ( P =0.036). RE did not have a significant impact on regional fat mass changes ( P ⩾0.055). In RVE, increases in visceral adipose tissue (−14%; P =0.028 vs inactive subjects) and in the arms (arms −8%, P =0.011 vs inactive) were not seen. We conclude that inactivity leads to a preferential increase in visceral adipose tissue.